2015
DOI: 10.1063/1.4922637
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanical transduction and characterization of a silica microsphere pendulum via evanescent light

Abstract: Dissipative optomechanics has some advantages in cooling compared to the conventional dispersion dominated systems. Here, we study the optical response of a cantilever-like, silica, microsphere pendulum, evanescently coupled to a fiber taper. In a whispering gallery mode resonator the cavity mode and motion of the pendulum result in both dispersive and dissipative optomechanical interactions. This unique mechanism leads to an experimentally observable, asymmetric response function of the transduction spectrum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
(44 reference statements)
3
23
0
Order By: Relevance
“…7a-e, the coupling gap is increased and the period of the CRUS becomes larger. The taper introduces a dispersive red shift to the microsphere's resonance [38]. In our experiments, the laser is blue-detuned relative to the resonance and fixed; the larger the distance between the WGR and the taper, the less the dispersion introduced; thus, the cavity mode shifts relative to the laser thereby decreasing the beat frequency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7a-e, the coupling gap is increased and the period of the CRUS becomes larger. The taper introduces a dispersive red shift to the microsphere's resonance [38]. In our experiments, the laser is blue-detuned relative to the resonance and fixed; the larger the distance between the WGR and the taper, the less the dispersion introduced; thus, the cavity mode shifts relative to the laser thereby decreasing the beat frequency.…”
Section: Methodsmentioning
confidence: 99%
“…In the supplementary material of Ref. [38], it was shown that the dispersive shift rate increases exponentially when moving to a strongly overcoupled regime. This means that the dispersive influence of the taper will induce a very large frequency shift for the cavity mode and the changes in the Gaussian term in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Typical one-port optical systems are a Fabry-Pérot system with one partially reflective mirror and one perfectly reflective mirror [see Fig. 1(c)] [25], all-pass ring resonators [19], and whispering gallery mode resonators coupled to an optical fiber [18]. The temporal dynamic of the intracavity complex field amplitude a(t ) is governed by the input-output relation [1,26]…”
Section: Coupled Equations Of Motionmentioning
confidence: 99%
“…This scheme was first proposed theoretically in the context of optomechanical cooling as an alternative to dispersive coupling in the so-called unresolved sideband limit [7], and also for its squeezing ability [8][9][10]. This coupling mechanism was implemented experimentally in diverse configurations such as Michelson-Sagnac interferometers [11][12][13][14], whispering gallery mode resonators coupled to a nanomechanical beam waveguide [15][16][17][18], ring resonators coupled to a micromechanical resonator [19], and photonic crystal (PhC) systems [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…By testing the prototype on a vehicle, we, to the best of our knowledge, achieved the first inertial measurements with a cavity optomechanical system out of the laboratory environment. We also demonstrated, for the first time, that the tapered waveguide can survive shocks of ±60 g, which would be of interest for many WGM [5,7,13,17,18,19,20,21,22] and photonic crystal experiments [6].…”
Section: Introductionmentioning
confidence: 99%